Oral CorticoSteroid sparing with biologics in severe asthma: A remark of the Severe Asthma Network in Italy (SANI) - Giorgio Walter Canonica (World Allergy Organization Journal, 2020)
According to the data derived from several national and international registries, including SANI (Severe Asthma Network Italy), and considering the strong impact that frequent or regular use of oral corticosteroid has on quality of life (QoL) of severe asthmatics, as well as on the costs for managing corticosteroid-related diseases, oral corticosteroid sparing up to withdrawal should be considered a primary outcome in the management of severe asthma. New biologics have clearly demonstrated that this effect is possible, with concomitant reduction in the rate of exacerbations and in symptom control. Then, there is no reason for using so frequently oral corticosteroid before having explored all alternatives currently available for a large part of severe asthmatics.